CPM 4. Increasing Cassava Farmers’ Income in the Philippines through Effective Nutrient Management (The Philippine Journal of Crop Science, 2018)
Cassava has a huge potential for rural industrial development and improving farmers’ income because of its contribution to food security and many industrial uses. Effective nutrient management is necessary to ensure that the crop is provided with the nutrients needed for its growth and development and prevent soil degradation. A balanced fertilizer application strategy must consider the factors influencing cassava nutrient requirements such as attainable yield and the crop’s response to fertilizer. The 4R nutrient stewardship concept provides guidance on applying the right source of plant nutrients at the right rate, at the right time, and in the right place. We conducted on-station and on-farm nutrient omission trials since 2014 to collect soil and agronomic data that are important in developing field-specific 4R-based fertilizer recommendations. Attainable yield ranged from 18-98 tons of fresh root yield ha; whereas yield in nutrient omission treatments ranged 6-68, 11-69, and 11-70 tons of fresh root yield per ha in minus N, minus P, and minus K, respectively. Results of nutrient omission trials were used to develop the beta version of Nutrient Expert Ⓡ Cassava (NECPH) – a decision support tool that enables crop advisors to rapidly develop 4R-based fertilizer recommendations for cassava using existing and readily-available site and farming information. Initial field testing of NECPH was conducted using Lakan-1 variety in sandy soils of San Narciso, Zambales with the treatments: full NPK, 4R High, +Manure, 4R High+Manure, 4R Low+Manure, and unfertilized control. Average cassava fresh root yield was highest with NPK (39 t/ha) and 4R High+Manure (37 t/ha) while it was lowest with the unfertilized control (23 t/ha). Gross profit above fertilizer cost obtained were Php 253,045, Php 239,638, Php 206,027, Php 209,322, Php 193,914, and Php 161,428, respectively. The 4R-based recommendations generated by NECPH were effective in increasing cassava yields and profitability in low-fertility soils.